Strategies of Parents, Teachers, and Schools to Develop a Superior Generation Alpha for Society 5.0 (Qualitative Study in Muhammadiyah Inovatif Baturetno Elementary School) - Putri, Mutia Eka; Khozin, Khozin (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2025)
There are many materials that must be taught appropriately, especially to elementary school children today. Elementary school students are now growing and developing as digital natives because they are accompanied by the rapid advancement of digital technology since birth. In addition to families, schools also have a fairly central role in adapting and taking action to prevent and handle various problems that arise due to the unwise use of smartphones by students. This article was written to explore what challenges and strategies must be taken by parents, teachers, and schools in teaching Alpha generation students. This paper specifically examines the methods of parents, teachers, and schools related to the research location, namely SD Muhammadiyah Inovatif Baturetno. This article is compiled using descriptive qualitative research. The researcher conducted a literature study that was strengthened by a field study at SD Muhammadiyah Inovatif Baturetno through interviews and observations. The results of the study showed that some upper-class students, namely grades 4, 5, and 6, have personal smartphones. It can be seen that parents have given their children the freedom to access the world without limits. The main task of teachers in this era is very important, not only in creating habits, providing examples, instilling commendable morals, but also teaching students in the classroom in the right way according to the characteristics of the digitally literate generation (generation Alpha). SD Muhammadiyah Inovatif Baturetno has mobilized teachers to teach students interactively and contextually and has carried out various school programs to produce students in the Alpha generation category who are expressive, critical, adaptive, collaborative, have character, and remain based on Islamic values.